Fluctuating asymmetry in the otolith dimensions of Lutjanus bengalensis (Lutjanidae) collected from muscat coast on the sea of Oman - L. Jawad; J. Al-Mamry; D. Al-Mamary (ՀՀ ԳԱԱ հրատ.)
The otolith length and width of adult teleost Lutjanus bengalensis were used to calculate the fluctuating asymmetry in these two characters. The results showed that the level of asymmetry of the otolith width was the highest among the two asymmetry values obtained for the otolith of Lutjanus bengalensis. Lutjanus bengalensis հասուն ձկան օթոլիտի մոտ երկարությունն ու լայնքը օգտագործվել են հաշվարկելու այդ երկու պարամետրերի Ֆլուկտուացող ասիմետրիան: Длина и ширина отолита взрослой рыбы Lutjanus bengalensis применялись для расчета флуктуирующей асимметрии этих двух параметров. Результаты показали, что уровень асимметрии ширины отолита самый высокий среди двух значений ассиметрии отолита, полученного у рыбы Lutjanus bengalensis.
Keywords: Biology